2022
DOI: 10.1002/ana.26300
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Numbers of Corticotropin‐Releasing Hormone Neurons in Narcolepsy Type 1

Abstract: Narcolepsy type 1 (NT1) is a chronic sleep disorder correlated with loss of hypocretin(orexin). In NT1 post‐mortem brains, we observed 88% reduction in corticotropin‐releasing hormone (CRH)‐positive neurons in the paraventricular nucleus (PVN) and significantly less CRH‐positive fibers in the median eminence, whereas CRH‐neurons in the locus coeruleus and thalamus, and other PVN neuronal populations were spared: that is, vasopressin, oxytocin, tyrosine hydroxylase, and thyrotropin releasing hormone‐expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…However, strong behavioral arousal is required in stressful situations, and PVH CRH neurons actively mediate stress-induced insomnia via the PVH CRH →LHHcrt pathway [8]. The above studies provide evidence to support the role for the PVH in controlling sleep–wake states from three aspects, as suggested from human clinical observations [29, 30] and animal experiments.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, strong behavioral arousal is required in stressful situations, and PVH CRH neurons actively mediate stress-induced insomnia via the PVH CRH →LHHcrt pathway [8]. The above studies provide evidence to support the role for the PVH in controlling sleep–wake states from three aspects, as suggested from human clinical observations [29, 30] and animal experiments.…”
Section: Discussionmentioning
confidence: 81%
“…1(c)] [29], indicating disrupted sleep structures following lesions. Another clinical observation reported that there was a substantial loss (97%) of hypocretin-1 immunoreactive and CRH neurons (88%) in the PVH, along with markedly less CRH-positive fibers in the ME, in narcolepsy type 1 postmortem brains [30]. In contrast, other major neuronal types (AVP, orexin/hypocretin, tyrosine hydroxylase, and TRH) in the PVH were unaffected [30].…”
Section: Lesion Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with PD, AD, Kleine-Levin Syndrome, and idiopathic hypersomnia, in which LH orexinergic and PB glutamatergic neurons are thought to function normally, still show hypersomnolence ( Bollu et al, 2018 ). Furthermore, dysfunctions of the PVH induced hypersomnia-like behaviors in mice ( Chen et al, 2021 ) and patients with narcolepsy type 1 showed reduced numbers of corticotropin-releasing hormone neurons in the PVH ( Shan et al, 2022 ), further supporting the importance of the PVH in arousal controlling and maintenance. Therefore, our case report first provides clinical evidence that dysfunctions of the PVH area led to hypersomnia in patients.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, some studies reported the association between AQP4-IgG, MOG antibodies and hypersomnia ( Kaur et al, 2013 ; Bollu et al, 2018 ; Chen et al, 2021 ) or disorder associated with MOG antibodies and hypersomnia ( Liu et al, 2020 ), with regression of hypersomnia after appropriate treatment of the autoimmune disease. On the other hand, it has been recently shown that an up-regulation of anti-MOG antibodies can be modulated by prolactin ( Shan et al, 2022 ), a hormone correlated with the onset of hypersomnia ( Kume et al, 2015 ). These findings indicated the potential role of the inflammatory/autoimmune pathogenesis underlying hypersomnia in these three cases with lesions of PVH area.…”
Section: Discussionmentioning
confidence: 99%